Description of four cases of male genital schistosomiasis (MGS) in children and adolescents, with a scoping review - Joachim Richter; Sekeleghe A. Kayuni; J. Russell Stothard; Charles Émile Ramarokoto; Andreas K. Lindner; Daniela Fusco; Hermann Feldmeier; Amaya L. Bustinduy; Jennifer F. Friedman (Parasitology)
We present four cases of male genital schistosomiasis (MGS) within children and adolescents opportunistically encountered as part of a wider screening programme for imported schistosomiasis in Germany and community outreach screening in Mali. Such genital manifestations in young children and adolescents are often overlooked but can include hydrocele, hypogonadism, varicocele, cutaneous granulomata on the penis and scrotum, echogenic spots in the prostate and the epididymis, alongside testicular masses. Though these cases appear sporadic, from our scoping literature review, they draw fresh attention on MGS in young children and highlight wider confusion with other congenital, neoplastic and infectious disease. These might include an insufficient closure of the tunica vaginalis, malignancies or lymphatic filariasis. Frequently haematuria is not present. One typical sign indicating MGS in adults, i.e. haematospermia is not present before puberty. Another reason of missing MGS cases may be that screening with scrotal or transabdominal ultrasonography are not easily accepted unless the reason for it is not extensively explained beforehand and that transabdominal ultrasonography is less sensitive for revealing prostatic lesions than transrectal ultrasonography.